Red de sensores inalámbricos multisalto para sistemas domóticos de bajo costo y área extendida (2017)
Wireless sensor networks have a wide range of applications and many pending challenges, especially those related to the evolution of digital electronics, bandwidth, reduction of implementation costs, network coverage and processing capacity. This document proposes a configuration of multi-hop wireless network oriented to intelligent domotic installations, based on 32-bit microcontrollers and low cost wireless communication modules, which allows to have complete coverage between the devices of the home automation system with a reduced loss of data, improvement in the processing capacity, adaptability and scalability in the nodes. The evaluation of network performance considers the following metrics: response time, network reach, scalability and precision. The experimental results determined a successful adaptation of the AODV multi-hop protocol, allowing sufficient coverage for a single-family house, at transmission speeds of 250Kbps, which guarantees the integrity and security of the data.